Efektivitas Dual-Task Training Motorik-Kognitif dalam Menurunkan Risiko Jatuh pada Lansia - Nahdiah Purnamasari (Media Kesehatan Masyarakat Indonesia, 2019)
The aging process causes a setback of various aspects of the body both physically, mentally andpsychologically which indirectly threatens the independence of the elderly and makes them vulnerable to fall.Exercise is generally useful in increasing muscle strength and improving balance and gait in order to reduce therisk of falls. The dual-task motor-cognitive exercise amalgamates physical and cognitive training together andinduces synergistic effects when combined in one intervention. This study aimed to determine the effect of dual-tasktraining on the risk of falls in the elderly. The method used was pre-experimental with one group pre-test post-testdesign with a duration of treatment for 4 weeks with a frequency of 3 times a week. Before and after treatment,respondents measured the level of balance and risk of falling using the Berg Balance Scale (BBS), Timed-Upand Go tests (TUGT), and Tinetti Balance Assessment Tool. The results showed an increase in the balance of theelderly after giving 12 exercises based on BBS (p <0.001) and TUGT (p=0.079). The risk of falls seems to declineafter 12 treatments (p <0.001). The highest reduction in risk of falls occurred after the first 6 treatments (p=0.011).It can be concluded that dual-task motoric-cognitive training is significantly influential in reducing the falling riskin the elderly.